The Validity and Efficacy of a Preventative Intervention Model for Reducing Ulcer Recurrence in Diabetic Patients in Indonesia - Suriadi Jais RN, PhD, AWCS, WOC, CFC; Kharisma Pratama RN, MSN, WOCN; Jaka Pradika RN, MSN, WOCN; Haryanto Haryanto RN, PhD, WOCN (SAGE Publishing, 2023)
Introduction It is important to reduce foot problems by preventing the recurrence of ulcers in diabetes mellitus (DM) patients. In Indonesia, interventions for the prevention of ulcer recurrence remain scarce. Objective The present study aimed to evaluate the validity and efficacy of a proposed intervention model for preventing the recurrence of ulcers in DM patients. Method Sixty-four DM patients were selected to participate in this quasi-experimental study and divided into two groups: intervention ( n   =  32) and control ( n   =  32). The intervention group received preventive treatment while the control group received standard care. Two trained nurses supported this study. Results Of the 32 participants in the intervention group, 18 (56.20%) were male, 25 (78.10%) were non-smokers, 23 (71.90%) had neuropathy, 14 (43.80%) had foot deformities, four (12.50%) had recurring ulcers, and 20 (62.50%) had a previous ulcer  < 12 months ago. Of the 32 participants in the control group, 17 (53.10%) were male, 26 (81.25%) were non-smokers, 17 (46.90%) had neuropathy, 19 (69.40%) had foot deformities, 12 (37.50%) had recurring ulcers, and 24 (75.00%) had a previous ulcer < 12 months ago. The mean (SD) age [62 (11.28) and 59 (11.11) years], ankle-brachial index [1.19 (0.24) and 1.11 (0.17)], HbA1C [9.18 (2.14%) and 8.91 (2.75%)], and DM duration [10.22 (6.71) and 10.13 (7.54)] of the intervention and control groups did not differ significantly. The content validity of the proposed intervention model was strong (I-CVI > 0.78). When the proposed screening tool for predicting the risk of ulcer recurrence in DM patients (NASFoHSkin) was used in the intervention group, its predictive validity, sensitivity, and specificity were 4, 100%, and 80%, respectively, while in the control group it was 4, 83%, and 80%, respectively. Conclusion Inspection/examination, foot care, and blood glucose control can decrease ulcer recurrence in DM patients.